3x-9=5x+2

Simple and best practice solution for 3x-9=5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-9=5x+2 equation:


Simplifying
3x + -9 = 5x + 2

Reorder the terms:
-9 + 3x = 5x + 2

Reorder the terms:
-9 + 3x = 2 + 5x

Solving
-9 + 3x = 2 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-9 + 3x + -5x = 2 + 5x + -5x

Combine like terms: 3x + -5x = -2x
-9 + -2x = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-9 + -2x = 2 + 0
-9 + -2x = 2

Add '9' to each side of the equation.
-9 + 9 + -2x = 2 + 9

Combine like terms: -9 + 9 = 0
0 + -2x = 2 + 9
-2x = 2 + 9

Combine like terms: 2 + 9 = 11
-2x = 11

Divide each side by '-2'.
x = -5.5

Simplifying
x = -5.5

See similar equations:

| -1.08=0.9v | | 2x+2y=2x+9 | | 4x^2-8x+4y^2+12y-131=0 | | 6s+2=-10 | | K-7+6= | | 12n-17n+6=32 | | v^2-4vx-12x^2=0 | | 3x(2)=12+5x | | 96=16+2x | | 9(t-6)+3=6(2t+3)-9 | | (17b-5)-4(4b+4)=-6 | | (X^2+4)=25 | | 2a+8a=8 | | (2x-4)-(5x+3)= | | 4c-43=7c-193 | | 44=4(x-5) | | -43=2+9x | | 3(y-7)=2(4+y) | | 4m=m+21 | | 20x^2-25+5= | | -2=4r-s | | 4(j-3)=23-3j | | 2x+5(x-18)=-174 | | 90=-8y+50 | | -5a+3=1 | | 2m=5m+60 | | -3(v+9)=-8v+8 | | 2-5x=3x-86 | | -5x-2(-6x+10)=-97 | | h(x)=4c^2+4c-3 | | 7x^2+119x+140=0 | | 5(7)-9-2= |

Equations solver categories